WILL THE IMPLEMENTATION OF A TOTAL QUALITY MANAGEMENT SYSTEM BENEFIT SOUTH AFRICAN CONSTRUCTION COMPANIES? - Joubert, W.; Cruywagen, J.H.; Basson, G.A.J. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The increased levels of competition experienced in recent times in the construction sector due to globalisation and the economic downturn highlighted the need for South African construction companies to be more competitive. This paper investigates the reasons for poor quality in the South African construction industry and whether the implementation of a Total Quality Management system in this industry will improve the situation. AFRIKAANSE OPSOMMING: Die ho